The complete mitochondrial genome of the Epaulette Shark, Hemiscyllium ocellatum (Bonnaterre, 1788) - Ryan J. Nevatte; Jennalee A. Clark; Jane E. Williamson; Michael R. Gillings (Mitochondrial DNA. Part B. Resources, 2019)
We present the complete mitochondrial genome of the Epaulette Shark Hemiscyllium ocellatum, sequenced with 24 primer sets. The 16,728 bp long circular genome consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a non-coding control region. Several protein-coding genes ended with incomplete stop codons (TA- or T–). Phylogenetic analysis indicated that H. ocellatum clusters within the Hemiscylliidae clade but separately from members of its sister genus Chiloscyllium. Utilization of the genome and primer sets presented here will be beneficial to future molecular studies involving H. ocellatum and other members of the Orectolobiformes.